2003
DOI: 10.1063/1.1578059
|View full text |Cite
|
Sign up to set email alerts
|

Photoinduced intermolecular electron transfer from aromatic amines to coumarin dyes in sodium dodecyl sulphate micellar solutions

Abstract: Photoinduced intermolecular electron transfer interaction between coumarin dyes and aromatic amines has been investigated in sodium dodecyl sulphate micellar solutions using steady-state and time-resolved fluorescence quenching measurements. Steady-state fluorescence quenching of the coumarin dyes by the amine quenchers always shows a positive deviation from linear Stern-Volmer relationship, which arises due to the localized high quencher concentrations at the micellar Stern layer. In time-resolved fluorescenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
184
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(197 citation statements)
references
References 76 publications
13
184
0
Order By: Relevance
“…7,9,11,15 Moreover, it has been shown that the inversion region of the Marcus correlation curve can be suitably tuned by changing the characteristics of the micellar media. 10,88 For different coumarin dyes in CPC micelle, the correlation of the fastest ET rates, i.e., the inverse of the first component of the ET times (k et ≈ τ 1 -1 ) with the ∆G 0 values of the ET reactions, is shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,9,11,15 Moreover, it has been shown that the inversion region of the Marcus correlation curve can be suitably tuned by changing the characteristics of the micellar media. 10,88 For different coumarin dyes in CPC micelle, the correlation of the fastest ET rates, i.e., the inverse of the first component of the ET times (k et ≈ τ 1 -1 ) with the ∆G 0 values of the ET reactions, is shown in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it helps us to observe the bell-shaped Marcus correlation curve for intermolecular ET reactions easily in microheterogeneous media, without increasing the reaction exergonicity (-∆G 0 ) to an unreasonably high value. 7 Additionally, in organized assemblies, the tethering of the reactants within the surfactant chains causes a large retardation in the rate of reactant diffusion, making the ET reactions to occur effectively under nondiffusive condition. [7][8][9][10][11]15 In one of our recent studies, it was observed that, for intermolecular ET reactions in different noninteracting micelles, the fastest ET time corresponding to the maxima of the Marcus correlation curves is only in the range of about 4 ps.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DMA is a very good electron donor, neutral in nature and sparingly soluble in aqueous solution [38,[54][55][56][57][58][59][60]. However, in the presence of CTAB micelles, the solubility of DMA has drastically increased.…”
Section: Reductive Quenching In Cationic Micelle Ctabmentioning
confidence: 99%
“…[27][28][29] Several groups also reported fluorescence quenching electron transfer in micelles. [30][31][32][33] It is well known that fluorescence quenching process of Coumarin dyes by DMA occurs due to the photoinduced electron transfer from DMA to the excited Coumarin dyes. [34][35][36][37][38][39][40] In the present study we observed a slower fluorescence quenching electron transfer rate due to the formation of proteinsurfactant complex as compared to the pure micellar solution.…”
Section: Introductionmentioning
confidence: 99%